2018
DOI: 10.1038/s41598-018-31069-2
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosine kinase receptor TIE-1 mediates platinum resistance by promoting nucleotide excision repair in ovarian cancer

Abstract: Platinum resistance is one of the most challenging problems in ovarian cancer treatment. High-throughput functional siRNA screening identified tyrosine kinase with immunoglobulin-like and EGF-like domains 1 (TIE-1) as a gene that confers cells resistant to cisplatin. Conversely enforced over-expression of TIE-1 was validated to decrease cisplatin sensitivity in multiple ovarian cancer cell lines and up-regulation of TIE-1 was correlated with poor prognosis and cisplatin resistance in patients with ovarian canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 38 publications
1
22
0
Order By: Relevance
“…It is hardly surprising, therefore, that upregulation of NER mediates resistance to cisplatin-based therapy [2,157]. Ishibashi et al reported that in OvC cell lines, tyrosine kinase with immunoglobulin-like and EGF like domains 1 (TIE1) promotes XPC-dependent NER and this leads to decreased susceptibility to cisplatin-induced cell death [158]. Last but not least, a study in 559 EOC patients showed an association of ERCC1 polymorphisms rs11615 and rs3212986 with cisplatin resistance Zhao et al analysed 17 SNPs in NER genes XPA, XPC, XPD/ERCC2, XPF/ERCC4, XPG, and ERCC1 in 89 OvC cases and 356 controls, and their results suggested that ERCC1, XPC, and XPD/ERCC2 may be linked to OvC susceptibility [154].…”
Section: Nucleotide Excision Repairmentioning
confidence: 99%
“…It is hardly surprising, therefore, that upregulation of NER mediates resistance to cisplatin-based therapy [2,157]. Ishibashi et al reported that in OvC cell lines, tyrosine kinase with immunoglobulin-like and EGF like domains 1 (TIE1) promotes XPC-dependent NER and this leads to decreased susceptibility to cisplatin-induced cell death [158]. Last but not least, a study in 559 EOC patients showed an association of ERCC1 polymorphisms rs11615 and rs3212986 with cisplatin resistance Zhao et al analysed 17 SNPs in NER genes XPA, XPC, XPD/ERCC2, XPF/ERCC4, XPG, and ERCC1 in 89 OvC cases and 356 controls, and their results suggested that ERCC1, XPC, and XPD/ERCC2 may be linked to OvC susceptibility [154].…”
Section: Nucleotide Excision Repairmentioning
confidence: 99%
“…Moreover, TIE-1 overexpression was observed in many types of cancer, including gastric- [14,15], colon- [16], and breast-cancer cells [17], but the significance of TIE-1 overexpression in cancer remains unknown. We previously reported that TIE-1 promotes DNA damage repair, thereby rendering ovarian-cancer cells resistant to cisplatin [18]. Therefore, TIE-1 might be a potential target for anticancer treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Drug resistance is attributed to high mortality in a number of other cancers besides NSCLC, including ovarian, breast, and colorectal cancer [10]. In ovarian cancer, Tie1, which forms part of the tyrosine kinase with immunoglobin and EGF homology domains (TIE) signaling pathway, was found to be involved in platinum-resistance and its high expression was correlated with a signi cantly poor prognosis [11]. Ishibashi et al [11] found that overexpression of Tie1, upregulates nucleotide excision repair to counteract the DNA-adduct damage and subsequent apoptosis caused by cisplatin and other platinum agents.…”
Section: Introductionmentioning
confidence: 99%
“…In ovarian cancer, Tie1, which forms part of the tyrosine kinase with immunoglobin and EGF homology domains (TIE) signaling pathway, was found to be involved in platinum-resistance and its high expression was correlated with a signi cantly poor prognosis [11]. Ishibashi et al [11] found that overexpression of Tie1, upregulates nucleotide excision repair to counteract the DNA-adduct damage and subsequent apoptosis caused by cisplatin and other platinum agents. Tie1 encodes a tyrosine kinase receptor that not only has involvement in drug resistance but may also function in tumorigenesis [12].…”
Section: Introductionmentioning
confidence: 99%